REVIEW: EVALUASI RASIONALITAS PENGGUNAAN OBAT ANTIHIPERTENSI DI BEBERAPA RUMAH SAKIT DI INDONESIA - Gusdilla, Windy; Hermanto, Faizal (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Approximately 1 billion people, or about a quarter of the world's adult population, are estimated to suffer from hypertension, and this number continues to grow. By 2025, the number of people with hypertension is predicted to reach 1.6 billion. Inaccuracy in the use of drugs can lead to increased morbidity and mortality, especially in patients with chronic diseases. Therefore, the selection of drugs must always follow the established treatment standards. This review article aims to evaluate the rationality of the use of antihypertensive drugs in several hospitals in Indonesia. The method used is a narrative literature review through a search of 11 articles with publication years 2019-2024. Literature searches were conducted on the Google Scholar, PubMed, and ScienceDirect databases. The keywords used in the search are